PERFORMANCE OF PUBLIC AREA SECTION EMPLOYEES IN THE HOUSKEEPING DEPARTMENT AT THE ZURI HOTEL PEKANBARU - Marzuki, Ali Asraf; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Public Area employee performance at The Zuri Pekanbaru has the duty and responsibility to maintain the cleanliness, tidiness, beauty and comfort of all areas of the hotel, both outside the building and inside the building, with the exception of guest rooms and kitchens. Public areas or common areas in a hotel are places that are frequently visited and used by guests, both staying and non-staying guests. Guests will judge and get a first impression from what they see and what they get from the public area. Cleanliness, neatness and comfort of public areas are the first impression for guests, which gives the image that the hotel they are visiting is a good hotel, which can give guests satisfaction during their stay at the hotel. This research aims to determine the factors that influence the performance of public area section employees. This research uses a qualitative method with a descriptive approach to describe and display the conditions that exist at a research site by collecting data and information obtained directly from the field. The key informants in this research are the Housekeeping Manager, Supervisor, employees and guests. In this research, the data collection techniques used were interviews, observation and documentation. From this research. From the research results obtained, the performance of public area section employees in housekeeping at The Zuri Hotel Pekanbaru is quite good. This indicates that employees are trying to work optimally. This can be seen, among others, through: the quality and quantity of employee work, neat implementation of tasks, a sense of responsibility for work, cooperative relationships between employees, superiors and co-workers. Keywords: Hotel, Employee Performance, The Zuri Hotel Pekanbaru